2000
DOI: 10.1162/08989290051137530
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Based Training of Stimulus Detection Improves Color and Simple Pattern Recognition in the Defective Field of Hemianopic Subjects

Abstract: In a previously conducted randomized placebo-controlled trial, we were able to demonstrate significant visual field enlargement induced by restitution therapy in patients with cerebral lesions [Kasten, E., Wuest, S., Behrens-Bamann, W., & Sabel, B. A. (1998c). Computer-based training for the treatment of partial blindness. Nature Medicine, 4, 1083-1087.]. Visual field training was performed on a computer monitor for 1 hr per day over a period of 6 months. Since the procedure included only stimulation with whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…46-57 treatmentinduced visual field enlargement in patients seldom exceeds 5°, although a few cases have shown remarkable and stable restitution of the visual field. [48][49][50][51][52][54][55][56] this enlargement might be sufficient to improve the reading abilities of some patients with visual field defects; however, the degree of change is too small to reduce the visual exploration impairment. normal reading performance only requires a visual field sparing of 3° to the left and 5° to the right of a fixation, 11,26,58 but the critical left-sided and right-sided visual field requirements in visual exploration are at least 20°.…”
Section: Nature Of Reading Impairmentsmentioning
confidence: 99%
“…46-57 treatmentinduced visual field enlargement in patients seldom exceeds 5°, although a few cases have shown remarkable and stable restitution of the visual field. [48][49][50][51][52][54][55][56] this enlargement might be sufficient to improve the reading abilities of some patients with visual field defects; however, the degree of change is too small to reduce the visual exploration impairment. normal reading performance only requires a visual field sparing of 3° to the left and 5° to the right of a fixation, 11,26,58 but the critical left-sided and right-sided visual field requirements in visual exploration are at least 20°.…”
Section: Nature Of Reading Impairmentsmentioning
confidence: 99%
“…While it is true that patients suffering from primary sensory damage can often compensate for their de®cits via appropriate eye and head movements, estimates of the percentage of hemianopic patients that exhibit spontaneous visual recovery have only ranged between 12 and 30% (see Chapter 2, Zihl, 2000). In contrast, two recent studies by Kasten and colleagues have shown that 1 hr of visual ®eld training per day over a 6-month period in patients with visual ®eld defects resulted in signi®cant enlargements of the visual ®eld, as tested via conventional perimetry, as well as some bene®ts in color and form recognition (Kasten, Poggel, & Sabel, 2000;Kasten, Wuest, Behrens-Bamann, & Sabel, 1998). Nonetheless, a substantial number of stroke patients suffer from cortical damage that compromises higher order visual and attentional abilities as well, particularly when the right hemisphere is affected (De Renzi, 1982;Posner, Walker, Friedrich, & Rafal, 1984;Robertson & Rafal, 2000;Zihl, 2000).…”
mentioning
confidence: 99%
“…Restitution aims to either restore function to the primary visual cortex or improve visual detection in nearby extra-striate visual pathways. This is typically undertaken with visual stimulation using extremely bright, high contrast stimuli [17]. Compensation aims to change behavior to compensate for lost visual function.…”
Section: Common Rehabilitation Approachesmentioning
confidence: 99%